PENGARUH MUTASI DAN PROMOSI JABATAN TERHADAP KINERJA ANGGOTA POLRI DI POLSEK BOJONGSARI DEPOK - Iis Nurrohmah; Dewi Retno Budiastuti (Journal of Research and Publication Innovation, 2025)
In this era of rapid globalization, human resource issues are a challenge for organizations or agencies because this development demands the importance of having good management and quality human resources for the progress of the organization. The data collection method in this study was obtained from primary data and secondary data Primary Data Primary data is data or information that is carried out directly by researchers, this primary data collection is usually done through questionnaires. The results of this study based on the results of the T test in the table above can be explained that the significance of the influence of X1 on Y gets a value of 0.009 where it is more <0.05 and gets a t count value of 2.737> 2.009 (t table). It can be concluded that Ha can be accepted which shows that there is an influence of mutation on member performance. Meanwhile, for the significant promotion, it gets a value of 0.503> 0.05 and gets a calculated value of 0.674 <2.009 (t table), it can be concluded that H0 can be accepted and Ha is rejected, which means that the promotion variable has no effect on performance. The results of the F test in the table above can be described in the f count pool getting a value of 12.550> 3.18 (f table) and getting a significant value of 0.000 <0.005, therefore it can be concluded that H3 can be accepted, which shows that there is an influence between variables X1 and X2 simultaneously on Y.